Character Reinforcement of Social Care Through Puluang Tradition in Wajok Hilir Village Mempawah - Tuti Alawiyah (Khatulistiwa, 2018)
Social care is an achievement outside of itself to help others or others through positive actions, eagerness, full of meaning and relationships that bind the community together. Along with the development of the times, the values of social care continue to experience degradation, especially among the younger generation or among students. To revive social care, the values related to togetherness need to be explored, namely the values contained in mutual cooperation activities. The mutual cooperation activities can be found in the people’s life of Wajok Hilir Village. This area is urban areas, located in Mempawah Regency. The population of this village consists of various tribes. This community is a village that has a majority of Bugis migrant from Sidendreng residents, Makasar. Puluang Tradition is a cultural custom that is still carried out by the Bugis tribe in Wajok Hilir Village. In tradition this usually occurs in an activity such as farming, marriage and building a new home. The tradition is full of social caring character values, such as being light-hearted, diligent, collaborating, having cooperation and being reciprocated.